Urbanization, environment and pharmaceuticals: advancing comparative physiology, pharmacology and toxicology. Issue 1 (17th January 2018) - Brooks, Bryan W
Abstract : Pharmaceuticals are indicators of a globally urbanizing water cycle. Unique physicochemical properties and biological activities of medicines diverge from traditional environmental contaminants, and thus challenge historical assessment approaches. Studies to understand environmental risks of pharmaceuticals benefit from mammalian pharmacology and toxicology data, and reciprocally advance basic and applied comparative efforts. Abstract: Pharmaceuticals are routinely reported in the environment, which indicates an increasingly urban water cycle and highlights a global megatrend. Physicochemical properties and intrinsic biological activity of medicines routinely differ from conventional organic contaminants; thus, diverging applicability domains often challenge environmental chemistry and toxicology computational tools and biological assays originally developed to address historical chemical stressors. Because pharmacology and toxicology information is more readily available for these contaminants of emerging concern than other chemicals in the environment, and many drug targets are conserved across species, leveraging mammalian drug discovery, safety testing and clinical pharmacology information appears useful to define environmental risks and to design less hazardous industrial chemicals. Research is needed to advance biological read across, which promises to reduce uncertainties during chemical assessment aimed at protecting public health and the environment. Whereas such comparative information has been critical to advance an understanding of pharmaceutical hazards and risks in urban ecosystems, studies of medicines with fish and other ecotoxicological models are reciprocally benefiting basic and translational efforts, advancing comparative mechanistic toxicology, and providing robust comparative bridges for integrating conservation and toxicology.